Inequities in the food consumption of the Brazilian population in the face of the COVID-19 pandemic - Vieira, Yohana Pereira; Gonzalez, Tatiane Nogueira; Melo, Luana Fernandes [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP]; Saes, Mirelle; Nogueira, Camila Castencio; Penteado, Júlia Oliveira (Springer Nature, 2025)
The COVID-19 pandemic worsened inequalities in healthcare, education, and housing, increasing extreme poverty and exposing ethnic and racial disparities. Access to nutritious food was also affected, particularly among vulnerable groups, including non-white individuals and women. Therefore, the primary objective of our study was to gain insight into the socioeconomic disparities in the consumption of fruits, vegetables, and soft drinks before and during the COVID-19 pandemic across all regions of Brazil. We conducted research using data from the Surveillance of Risk and Protective Factors for Chronic Diseases by Telephone Survey (VIGITEL) to analyze the consumption patterns of fruits, vegetables, and soft drinks/artificial juices before and during the pandemic, focusing on adults (aged 18–59 years) who regularly consume these items five or more days a week, and including information on skin color, age, marital status, sex, region of residence, and socioeconomic level. The sample consisted of 261,643 individuals. The period from 2012 to 2020 was classified as pre-pandemic, while 2021–2022 was considered the pandemic period. The findings significant role that socioeconomic inequalities play in shaping dietary habits, with notable differences associated with gender, skin color, educational attainment, marital status, and region of residence. Women who are non-white, have lower educational levels, are single, and reside in the northern and northeastern regions reported lower consumption of fruits and vegetables. Our data unequivocally highlight the pressing need for new, targeted public policies aimed at addressing food inequalities in Brazil. This need is particularly urgent following the pandemic, which has further exacerbated ethnic and social disparities in the country.
Keywords: COVID-19 pandemic; Dietary patterns; Food inequalities; Public health policies; Socioeconomic inequalities